Akhlak Education According to Ibnu Miskawaih (Education ‎Epistemology Perspective)‎ - Wahid Arbani (IAIN Salatiga, 2019)
The emergence of globalization and capitalism in our lives today has given rise to the emergence of hedonistic attitudes, consumerism, materialism and the emergence of permissive attitudes. This contemporary condition is clearly in a dangerous condition, so it is necessary to look for moral and moral principles to maintain the continuity of human life on this earth. One effort that can be done is to re-express the thoughts of classical Muslim leaders who have been able to exert influence in the development of the Islamic world and have even been able to bring glory to Islam. Ibn Miskawaih is one of the Muslim philosophers who in every major discussion of his writings always includes moral aspects, so it is interesting to study, how far the concept of moral education according to Ibn Miskawaih is able to parse various problems in the implementation of moral education in the present and future come. By using qualitative research methods through the documentation of the book Tahzib al-Aklaq Wa Tathir al-Arara, the conclusion is that the epistemology of moral education according to Ibn Miskawaih includes; sources of knowledge, benchmarks of truth and classification of knowledge, and methodologies for acquiring knowledge. The source of knowledge, according to Ibn Miskawaih, is epistemologically derived from the truth of revelation, although in his writings Ibn Miskawaih did not write the postulates of the Qur'an and al-Hadist directly.